Analisis Peralatan Persinyalan Kereta Api dengan Persinyalan Elektrik Silsafe4000 Di Stasiun Lempuyangan Yogyakarta (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2022)
Train signaling is used of a certain shape, color, or light to give the driver a message that will ensure a safe train journey. Upgrading the signaling infrastructure at stations all over Java and Sumatra. One of these entails updating the station's electrical signaling, which was previously constructed in 1986. Equipment spare components, which are challenging and frequently encounter problems that impair the system's dependability, are the primary factor being refreshed. This electrical signaling makes use of the SILSafe4000 system, which was created by PT LEN's youth. In this study, the researcher examined the cross-capacity calculations, equipment standardization, and questionnaires given to PPKA officers to investigate the SILSafe4000 electrical signaling reliability system at the lempuyangan station by making use of cross-capacity estimates, equipment standardization, and questions given to PPKA personnel about how challenging it is to operate the Lempuyangan HMI station. The necessary data was gathered by the researcher in advance of the study. Based on standardization of the equipment, BSG9 motor voltage standard and signal 110VAC±10%, detection voltage (inverse) 24VDC±10%, or range (21.6-26.4V DC), rated current < 10A, ground 5Ω, R≤50Ω, and insulation. That the following pieces of equipment have been standardized: the point motor's in-ER voltage is 78.94%, . the driving voltage is 89.47%, the signal voltage is 83.3%, the grounding is 100%, the cable resistance is 96%, and the cable insulation is 100%. Reliable electrical signaling can also support rail travel systems. Lempuyangan Station can accommodate 134 trains per day, with an average headway of 12.51 minutes, maximizing the traffic capacity of 116 trains KA>K is served with an electric signaling system safely and zero accident. Then a questionnaire was given to the officer regarding the difficulty level of operating the Lempuyangan HMI station, which was very easy with a score of 4.7/5.